2020
DOI: 10.1038/s41598-020-61359-7
|View full text |Cite
|
Sign up to set email alerts
|

Attention strengthens across-trial pre-stimulus phase coherence in visual cortex, enhancing stimulus processing

Abstract: Attention selectively routes the most behaviorally relevant information from the stream of sensory inputs through the hierarchy of cortical areas. previous studies have shown that visual attention depends on the phase of oscillatory brain activities. these studies mainly focused on the stimulus presentation period, rather than the pre-stimulus period. Here, we hypothesize that selective attention controls the phase of oscillatory neural activities to efficiently process relevant information. We document an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 86 publications
3
17
0
Order By: Relevance
“…Cognitive neurosciences and neuromarketing rely on gaze tracking ( Lim, 2018 ; Zareian et al, 2020 ; Parto Dezfouli et al, 2021 ; Veith et al, 2021 ); however, a proper solution has been missing due to the high number of degrees of freedom involved with the possible combinations of eye and head movements. Here, we showed that by using a recently introduced pose-estimation tool named DLC, the dimensionality of gaze tracking could be reduced considerably to estimate the point of gaze with a shallow artificial neural network.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive neurosciences and neuromarketing rely on gaze tracking ( Lim, 2018 ; Zareian et al, 2020 ; Parto Dezfouli et al, 2021 ; Veith et al, 2021 ); however, a proper solution has been missing due to the high number of degrees of freedom involved with the possible combinations of eye and head movements. Here, we showed that by using a recently introduced pose-estimation tool named DLC, the dimensionality of gaze tracking could be reduced considerably to estimate the point of gaze with a shallow artificial neural network.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we show that on high behavioral performance epochs, LFP alpha coherency is higher than on low behavioral performance epochs. Signal coherency within and between brain areas is proposed as a key mechanism at the core of brain computing functions and supports information/stimulus processing(Fries, 2015b), accounting for network connectivity(Vinck et al, 2010), and changes in behavioral performance(Zareian et al, 2018, 2020). Last, we report changes in spike field coherency within the prefrontal cortex between the epochs of high vs. low behavioral performance, in the same frequency ranges as reported by others during attention orientation(Fries et al, 2008; Gregoriou et al, 2009b; Paneri and Gregoriou, 2017), thus pointing to a direct modulation of attentional mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological details concerning our animal subjects, their holding and welfare, our experimental permits, surgeries and implants as well as details of the experimental setup were reported previously [16,70,[73][74][75]. We reiterate relevant details here:…”
Section: Methodsmentioning
confidence: 99%
“…For example, Montemurro et al previously reported that in the primary visual cortex (i.e., V1 of anaesthetized monkey), the phase of neuronal spikes (relative to low-frequency oscillations) provides additional information, exceeding the information that can be extracted from the spike rate alone [8]. Recent research has provided evidence for the significance of the interaction between the spike times and the oscillatory phase in the ongoing population activity in association with high-level brain functions, such as visual attention [9][10][11][12][13][14][15][16], sensory processing [17,18], decision making [19], and memory [20][21][22][23][24]. In addition to information encoding [24][25][26][27][28], this spike-phase coupling, as an indication of spike timing control, mediates the inter-neuronal synchronization of activity within a region, that is of particular importance for not only optimizing the inter-areal communication via the temporal coordination of postsynaptic potentials [29][30][31], but also the performance of subjects' perceptual decisions [32,33].…”
Section: Introductionmentioning
confidence: 99%